Peningkatan Hasil Belajar Peserta Didik Melalui Model Problem Based Learning - Rahmawati, Isna; Suwartini, Sri; Ferryka, Putri Zudhah; Rofisian, Nela (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2024)
The research objective of this research is to determine student learning outcomes after learning using the Problem Based Learning model. This research is motivated by problems in learning, especially science and science, namely the low learning outcomes of class V students. This problem is caused by the learning model used by educators being less innovative so that learning activities are less enjoyable, students only become listeners when the teacher explains the material. The benefits of this research can increase the insight and ability of educators in designing learning models and improving the quality of learning. This research is classroom action research using the Kemmis & Mc Taggart model. This research model consists of four stages, namely planning, implementing actions, observing and reflecting. The subjects in this research were class V students at SD N 2 Prambanan, consisting of 19 students. The data collection techniques for this research are observation using observation sheets, measuring learning outcomes, and c) documentation. The data analysis technique in this research uses descriptive analysis by reflecting the results of implementing the actions carried out in each cycle. The results in this research show an increase in learning outcomes in each cycle. The learning outcomes of students who had completed the first cycle were 14 students with a percentage of 73.58%. In cycle II there were 16 students who had completed it with a percentage of 84.21%. These results reveal a significant increase in student learning outcomes through the application of the Problem Based Learning learning model.